High‐dose Cepharanthin for pediatric chronic immune thrombocytopenia in Japan. Issue 3 (13th November 2016) - Yamazaki, Taro; Shibuya, Atsushi; Ishii, Saori; Miura, Nobuyuki; Ohtake, Akira; Sasaki, Nozomu; Araki, Ryuichiro; Ota, Yatio; Fujiwara, Mitsuhiro; Miyajima, Yuji; Uetake, Kimiaki; Hamahata, Keigo; et al.
Abstract: Background: A nationwide, multicenter and observational study was retrospectively conducted to evaluate the clinical utility of Cepharanthin (CEP) for pediatric patients with chronic immune thrombocytopenia (ITP). Methods: Clinical and laboratory data for 46 Japanese patients aged <16 years who were diagnosed as having chronic ITP in 14 hospitals during 2001–2011, and were treated with CEP for >12 months, were analyzed. Results: Median daily CEP dose was 1 mg/kg (range, 0.12–2 mg/kg). Median platelet count prior to CEP was 20.5 × 10 9 /L (IQR, 8.3–53.0 × 10 9 /L), and then significantly increased to 58.5 × 10 9 /L (IQR, 22.8–115.0 × 10 9 /L) and 69.0 × 10 9 /L (IQR, 23.0–134.0 × 10 9 /L) at 12 and 24 months of treatment, respectively. No life‐threatening bleeds or moderate–severe adverse events were reported. Of 38 patients who received both corticosteroids (CS) and CEP, 17 patients (45%) were weaned from CS, and 15 patients (39%) attained the reduced dose of CS. The duration from the start of CEP to the stopping of CS was a median of 413 days (range, 49–1734 days) in patients who were weaned from CS. Conclusions: CEP alone or combined with CS was useful for the management of pediatric chronic ITPs.